2008
DOI: 10.1099/mic.0.2008/017418-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the pSK1 replicon, a prototype from the staphylococcal multiresistance plasmid family

Abstract: Multidrug-resistant staphylococci often harbour plasmids that carry genes conferring resistance to several antimicrobial compounds. Many of these multiresistance plasmids appear to utilize a related theta-type replication system for which multiresistance plasmid pSK1 serves as a prototype. Essential pSK1 replication elements were identified by cloning segments of the replication region and testing the resulting plasmids for replication proficiency. An iterated region within rep and a DNA segment of up to 68 bp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 30 publications
(46 reference statements)
0
28
0
Order By: Relevance
“…No evidence was found to suggest that any of the four Rep boxes are involved in negative regulation of pSK41 replication, since all Rep box deletions reduced plasmid copy number. Given that replication of staphylococcal multiresistance plasmids such as pSK41 and pSK1 is controlled by an antisense RNA (Kwong et al, 2006(Kwong et al, , 2008, a role in the negative regulation of plasmid replication may not be required for the oriV iterons of these plasmids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No evidence was found to suggest that any of the four Rep boxes are involved in negative regulation of pSK41 replication, since all Rep box deletions reduced plasmid copy number. Given that replication of staphylococcal multiresistance plasmids such as pSK41 and pSK1 is controlled by an antisense RNA (Kwong et al, 2006(Kwong et al, , 2008, a role in the negative regulation of plasmid replication may not be required for the oriV iterons of these plasmids.…”
Section: Discussionmentioning
confidence: 99%
“…The RepA_N family includes a group of conjugative pheromone response plasmids from Enterococcus faecalis (De Boever et al, 2000;Francia et al, 2004;Hedberg et al, 1996), the vast majority of currently identified multiresistance plasmids from staphylococci Gering et al, 1996;Gill et al, 2005;Kwong et al, 2004Kwong et al, , 2008Zhang et al, 2003), as well as a number of plasmids from Lactococcus (Hagen et al, 2010), Lactobacillus (Thompson et al, 1999) and Bacillus (Tanaka et al, 2005). Several Rep proteins from this family have been shown to bind to repeated sequences that are located centrally within the rep gene, and these repeats have been shown to form part of the oriV (Francia et al, 2004;Kwong et al, 2004Kwong et al, , 2008Tanaka et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, looping within a single origin would require that RepA proteins bind to nonconsecutive iterons (e.g., iterons 1-3, 1-4, or 2-4). However, DNase I protection studies on RepA-origin interactions clearly revealed that when RepA binds, every box is protected, which would not be consistent with nonconsecutive looping (28)(29)(30). Moreover, the pattern of protection in the footprints is strikingly periodic, which indicates essentially identical modes of RepA binding to each iteron, in particular for boxes 2-4 in the pSK41 origin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…genus-specific clusters, suggesting that this domain may perform a host-specific role (28)(29)(30)(31)(32). Although the function of the RepA CTD remains enigmatic, recent studies have indicated that the NTD mediates DNA binding and interacts with iterons that reside within the plasmid origin (30).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation